Single‐Dose Pharmacokinetics and Tolerability of the Oral Epidermal Growth Factor Receptor Inhibitor Mobocertinib (TAK‐788) in Healthy Volunteers: Low‐Fat Meal Effect and Relative Bioavailability of 2 Capsule Products. Issue 9 (12th June 2021) - Zhang, Steven; Jin, Shu; Griffin, Celina; Feng, Zhongling; Lin, Jianchang; Baratta, Mike; Brake, Rachael; Venkatakrishnan, Karthik; Gupta, Neeraj
Abstract: Mobocertinib (TAK‐788) is a tyrosine kinase inhibitor under investigation for treatment of non–small cell lung cancer with activating EGFR exon 20 insertions. This study examined the safety; tolerability; pharmacokinetics (PK), including food effects; and bioavailability of mobocertinib in healthy volunteers. In part 1, fasted volunteers were randomized to placebo or mobocertinib in single‐ascending‐dose cohorts (20‐160 mg). In part 2, mobocertinib (120/160 mg) was administered on day 1 of periods 1 and 2 under fasted or low‐fat meal conditions (2‐period, 2‐sequence crossover design). In part 3, fasted volunteers received mobocertinib 160 mg in 1 of 2 capsule products on day 1 of periods 1 and 2 with 7‐day washout. Safety and PK parameters were assessed. Sixty‐nine volunteers were enrolled (mean age, 29 years; 75% male). The most common adverse events (AEs; ≥10% of volunteers) were gastrointestinal AEs (25%‐50%) and headache (8%‐31%). No serious AEs were reported. A low‐fat meal did not affect the PK of mobocertinib or its active metabolites. The geometric mean terminal disposition phase half‐life (20 hours) supported once‐daily dosing. The 2 capsule products were bioequivalent. These data guided dosing and supported administration of mobocertinib without regard to low‐fat meal intake in ongoing and planned clinical studies.